Kinematic contribution of the lower limb to vertical javelin velocity in male javelin throwers - Makino, M.; Tauchi, K. (ISBS Proceedings Archive (Michigan), 2022)
In the javelin throw, vertical release velocity is correlated with throwing record positively. The purpose of this study was to clarify the kinematic contribution of the lower limb to the vertical javelin velocity in male javelin throwers and to examine the movements that enhance the contribution of the lower limb. The throwing movements of 115 male javelin throwers were videotaped and analyzed using a three-dimensional motion-analysis technique. The vertical release velocity for each body part was expressed as the relative velocity. The vertical javelin velocity acquired by lengthening and rotation of the lower limb was calculated by applying an inverted pendulum model. The lower limb contributed positively to the vertical release velocity (12.2 ± 2.8%). The contribution of the lower limb was mainly acquired through rotation. Throwers with higher vertical release velocity showed greater contributions of both rotation and lengthening movements.